Into the history of Internet art (Electronic Superhighway. From Experiments in Art and Technology to Art After the Internet, 2016-1966; Whitechapel Gallery, Londýn) - Meixnerová, Marie (Iluminace, 2016)
Review of the London Electronic Superhighway exhibition. From Experiments in Art and Technology to Art After the Internet, 2016-1966, which took place from 29 January - 15 May 2016 at the Whitechapel Gallery.
Keywords: exhibitions; art development; new technologies; internet and film